الاقتباس وطرق توثيق مصادره في الهامش وفق أسلوب شيكاغو: دراسة تقييمية لعينة من الرسائل الجغرافية المنجزة بالأكاديمية الليبية (Journal of Academic Research, 2020)
The purpose of this study is to determine the rules and regulations of quotation and documentation in the margin according to the Chicago style. Due to its importance as a basic principle in geographic research, and to verify the adherence of the study sample to the rules of this type of citation and documentation in the scientific thesis completed in the geography departments of the Libyan Academy in Janzour and Misurata. By analyzing the results of the evaluation form prepared by researchers for this purpose. The results of the analysis showed that there was a variation in the adherence of the study sample to the basics and controls of the Chicago documentary method. Despite the difference between the subjects covered in the methodologies they studied and the differing views of the supervisors, there was agreement in some rules up to 100%.